Decline in cardiorespiratory fitness and its association with vascular aging and subclinical atherosclerosis in healthy older adults: a 3-year longitudinal study - Vincent Groesser; Christopher Weyh; Torsten Frech; Natascha Sommer; Klaus Eder; Astrid Most; Samuel Sossalla; Karsten Krüger; Pascal Bauer (GeroScience, 2026)
Aging is associated with progressive deterioration of vascular function and cardiovascular risk. Cardiorespiratory fitness (CRF) is closely associated with cardiovascular health, yet longitudinal data in healthy older adults remain limited. This study examined 3-year changes in vascular and echocardiographic parameters in older adults and their associations with CRF and muscle strength. Forty-nine participants (mean age 63.8 ± 3.8 years) underwent vascular assessments (brachial/central blood pressure (BP), pulse wave velocity (PWV), augmentation index), echocardiography, CRF testing via spiroergometry to determine VO 2 peak, muscle strength testing, and carotid sonography at baseline and after 3 years. Participants were grouped by carotid plaque status: no atherosclerosis, existing atherosclerosis, or newly developed atherosclerosis. Over 3 years, CRF and muscle strength (grip strength, leg flexion) declined significantly (all p < 0.005), while systolic BP ( p = 0.042), brachial-ankle PWV ( p = 0.006), and echocardiographic parameters including aortic root diameter and ventricular dimensions increased (all p < 0.001). Participants with newly developed atherosclerosis showed the greatest CRF decline ( p = 0.012). Changes in CRF were inversely associated with changes in systolic, diastolic, and central BP (all p < 0.01). Declines in leg flexion strength were also linked to larger BP increases. Participants maintaining > 90% of baseline VO 2 peak had significantly smaller BP increases. These results indicate that vascular aging progresses measurably within a few years in clinically healthy older adults and is associated with declines in CRF and muscle strength. Preservation of CRF is linked to more favorable vascular aging profiles and a lower prevalence of newly developed atherosclerosis. Graphical Abstract

Association of cardiorespiratory fitness level with vascular function and subclinical atherosclerosis in the elderly - Vincent Größer; Christopher Weyh; Tim Böttrich; Torsten Frech; Svenja Nolte; Natascha Sommer; Magdalena Huber; Klaus Eder; Oliver Dörr; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; et al. (European Journal of Applied Physiology, 2024)
Purpose Physical exercise is crucial for healthy aging and plays a decisive role in the prevention of atherosclerotic cardiovascular disease (ASCVD). A higher level of cardiorespiratory fitness (CRF) in the elderly is associated with lower cardiovascular and all-cause mortality. This study investigated the association of CRF level with vascular function and cardiovascular risk factors in the elderly. Methods We examined 79 apparently healthy and physically active subjects aged > 55 years (64 ± 4 years). Cardiovascular functional parameters assessed included brachial and central blood pressure (BP), pulse wave velocity (PWV), augmentation index (Aix), and ankle-brachial index. Sonography of the common carotid artery was performed. CRF level was determined by a cardiopulmonary exercise test, and everyday activity was quantified with an accelerometer. Results All participants had a higher CRF level than the reported age-specific normative values. Twenty-nine subjects had subclinical atherosclerosis of the common carotid artery. Compared with participants without atherosclerosis, they were older ( p = 0.007), displayed higher brachial systolic BP ( p = 0.006), and higher central systolic BP ( p = 0.014). Lower brachial ( p = 0.036) and central ( p = 0.003) systolic BP, lower PWV ( p = 0.004), lower Aix ( p < 0.001), lower body fat percentage (< 0.001), and lower LDL cholesterol ( p = 0.005) were associated with a higher CRF level. Conclusions In this cohort of healthy and physically active individuals, subjects with subclinical atherosclerosis displayed higher systolic brachial and central BP. A higher CRF level was associated with enhanced vascular function, consistent with an influence of CRF on both BP and vascular function in the elderly.

Effects of Traumeel (Tr14) on recovery and inflammatory immune response after repeated bouts of exercise: a double-blind RCT - Kerstin Muders; Christian Pilat; Vanessa Deuster; Torsten Frech; Karsten Krüger; Jörn Pons-Kühnemann; Frank-Christoph Mooren (European Journal of Applied Physiology, 2017)

Glucose inhibits the formation of gas vesicles in Haloferax volcanii transformants - Torsten Hechler; Miriam Frech; Felicitas Pfeifer (Environmental Microbiology, 2008)
Summary The effect of glucose on the formation of gas vesicles was investigated in Haloferax mediterranei and Hfx.volcanii transformants containing the mc‐ gvp gene cluster of Hfx. mediterranei (mc‐vac transformants). Increasing amounts of glucose in the medium resulted in a successive decrease in the amount of gas vesicles in both species, with a complete inhibition of their formation at glucose concentrations of > 70 mM in mc‐vac transformants, and 100 mM in Hfx. mediterranei . Maltose and sucrose imposed a similar inhibitory effect, whereas xylose, arabinose, lactose, pyruvate and 2‐deoxy‐glucose had no influence on the gas vesicle formation in mc‐vac transformants. The activities of the two mc‐vac promoters were strongly reduced in mc‐vac transformants grown in the presence of > 50 mM glucose. The gas vesicle overproducing ΔD transformant (lacking the repressing protein GvpD) also showed a glucose‐induced lack of gas vesicles, indicating that GvpD is not involved in the repression. The addition of glucose was useful to block gas vesicle formation at a certain stage during growth, and vice versa , gas vesicle synthesis could be induced when a glucose‐grown culture was shifted to medium lacking glucose. Both procedures will enable the investigation of defined stages during gas vesicle formation.